WASH and NTDs: Outcomes and lessons learned from the implementation of a formative research study in NTD skin co-endemic communities in Benin - Salou Bachirou, Zoulkifl; Mignanwande, Zinsou Franck; Bokossa, Hervé; Degnonvi, Horace; Djossou, Parfait; Hondjrebo, Flora; Amoukpo, Hermione; Anagonou, Esai Gimatal; Agbo, Inès; Toffa, Damien; Ba, Rafiatou; Gine, Anna; et al. (Frontiers in Medicine, 2023)
Neglected Tropical Diseases (NTDs) are a diverse group of bacterial, viral, parasitic and fungal diseases affecting people, most of whom live below the poverty threshold. Several control strategies are defined against these diseases, including chemotherapy and Water, Hygiene and Sanitation (WASH). This study assesses the effect of promoting hygiene and sanitation on soil-transmitted helminthiasis s and NTDs of the skin. It took place in the communes of Ze, Lalo and Zangnanado, three municipalities located in the south of Benin. This is a formative research that took place in three phases. The first phase entailed a baseline information and situational analysis of the state of hygiene and health, using soil-transmitted helminthiasis and wound hygiene practices as cases studies. In the second phase, interventions to promote improved hygiene and sanitation were implemented. The third phase was devoted to post-intervention evaluation. The situation analysis showed that the prevalence of soil-transmitted helminthiasis was 6.43% and 7.10% in the municipalities of Ze and Lalo respectively. In the communes of Zangnanado, the most common wound management practices identified were: putting sand or ashes in the wounds to keep flies away, the use of medicinal plants and the application of powder from antibiotic capsules for wound dressing. The post-intervention evaluation showed a decrease in the prevalence of soil-transmitted helminthiasis from 6.43% to 1.19% in the municipality of Lalo and from 7.10% to 1.75% in the municipality of Ze. In the commune of Zangnanado, a significant shift in wound management practices was noted, which led to the healing of several chronic wounds. This research supports the evidence that WASH-based interventions, in addition to specific diseases based interventions, are very important to tackle NTDs.